2016
DOI: 10.3390/nu8070385
|View full text |Cite
|
Sign up to set email alerts
|

The Erythrocyte Fatty Acid Profile and Cognitive Function in Old Chinese Adults

Abstract: Objective: To explore the relationship between the erythrocyte fatty acid profile and cognition in elderly Chinese adults. Methods: 60 mild cognitive impairment (MCI) subjects and 60 age- and gender-matched control adults (aged 55 years and above) were involved in this cross-sectional study. Cognitive function was measured by using the Montreal Cognitive Assessment (MoCA) test. Information regarding the demographic characteristics and lifestyle of the participants was collected with a questionnaire. A semi-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
2
8
1
Order By: Relevance
“…The study identified individuals with higher baseline erythrocyte membrane DHA levels had higher their brain volumes approximately 8 years later. Similar beneficial effects of DHA (erythrocyte membrane DHA levels) on brain among elderly / adults are reported in other studies as well [35,36]. These studies provide evidences for positive association between erythrocyte membrane DHA levels and brain volume, and possibly a beneficial role with regards to cognition.…”
Section: Pottala Et Al (2014) Documented Positive Association Betweensupporting
confidence: 86%
“…The study identified individuals with higher baseline erythrocyte membrane DHA levels had higher their brain volumes approximately 8 years later. Similar beneficial effects of DHA (erythrocyte membrane DHA levels) on brain among elderly / adults are reported in other studies as well [35,36]. These studies provide evidences for positive association between erythrocyte membrane DHA levels and brain volume, and possibly a beneficial role with regards to cognition.…”
Section: Pottala Et Al (2014) Documented Positive Association Betweensupporting
confidence: 86%
“…It is also attractive the fact that membranes are made of fatty acids, which are in their turn components of the nutrition, with the essential omega-6 and omega-3 polyunsaturated fatty acids (PUFA) especially important for the correct child growth. Moreover, fatty acids in membrane phospholipids are evaluated in many diseases, including neurological ones, finding out that RBC membranes give precious indications on omega-3 and other fatty acids that influence brain structures, functions and behavior 26 , 27 , 28 , 29 . Membrane fatty acid analysis in our ASD cohort evidenced a significantly different DHA level (ANOVA test, P value = 0.0344).…”
Section: Discussionmentioning
confidence: 99%
“…These include biomarkers associated with cell growth (insulin-like growth factor binding protein), pancreatic function (pancreatic polypeptide), stress (cortisol), 1-carbon metabolism (homocysteine), antioxidant function (superoxide dismutase), and kidney function (b-2 microglobulin) (13)(14)(15). Other studies showed strong associations of single FAs or combinations of specific SFAs, MUFAs, PUFAs, and v-3 FAs with MCI (16)(17)(18)(19). Such biomarkers, when combined with other risk factors such as age, sex, and APOE genotype may provide a stronger predictive potential for identifying those with an increased probability of MCI and AD.…”
Section: Current Status Of Knowledgementioning
confidence: 93%